The Effect of the Dog Breed Ban on Bite Incidences and the Usage of Rabies Post-Exposure Prophylaxis on Fort Riley - Collins, Hayley (My University, 2015)
This study evaluated the impact that the Banned Dog Breed Policy on Fort Riley military installation has had on the number of dog bite-related injuries seen in the emergency room at Irwin Army Community Hospital (IACH) and the amount of rabies post-exposure prophylaxis (PEP) used at any of the medical clinics on Fort Riley. The Policy was implemented on Fort Riley on 01 October 2008, banning American Staffordshire Terriers, Staffordshire Bull Terriers, Pit Bulls, and mixes of these breeds. This study also evaluated the average percentages of dog bite reports received by Veterinary Services by the next duty day per year and overall over a 10-year period. Data used to calculate the incidence rates and percentages were gathered from Public Health Command and Health Information Management. The population statistics were obtained from Residential Communities Initiative, Housing Division. Results show that the breed ban has made no significant difference in the incidence rates of dog bites, with an average incidence of 5.265 per 1,000 persons before the breed ban and 4.255 per 1,000 persons after the breed ban and an alpha of 0.982. There was an increase from 34 before the breed ban to 43 after the breed ban of number of people that initiated PEP. There was no linkage between the unpredictable number of PEP series’ initiated and the steadily growing population. There were a total of 701 dog bite reports from 2003-2012, of which 27.25% (191) were not received by Veterinary Services by the next duty day. This is vital to public safety due to the fact that staff at Veterinary Services are responsible for locating and quarantining an animal following a bite incident to minimize the risk of another incident occurring with the same dog, as well as the possibility of rabies exposure to another person from the same dog. Results indicate that the Banned Dog Breed Policy has not had the intended effects and that the rates at which reports are received by Veterinary Services need to increase in order to increase public safety.
Keywords: Public safety; Dog breed ban; Fort Riley; Public Health (0573)